The effect of unemployment duration on future earnings and other outcomes - Daniel Cooper (Federal Reserve Bank of Boston, 2014)
One of the distinguishing features of the Great Recession and its aftermath has been the spike in the number of individuals experiencing long-duration unemployment spells, defined as lasting more than 26 weeks. This paper analyzes the effect of unemployment duration on individual's future earnings and other outcomes, such as homeownership and wealth, using data from the Panel Study of Income Dynamics (PSID). The results show a negative relationship between a worker's most recent unemployment spell and his or her current earnings. The earnings of displaced workers do not catch up to those of their nondisplaced counterparts for nearly 20 years. The effect of unemployment on earnings is even more substantial for workers unemployed 26 weeks or more. Unemployment spells also negatively impact future homeownership - this finding suggests that the consequences of the recent spike in unemployment duration could affect more than individuals' expected lifetime earnings. Given the costs of long-term unemployment, policies aimed at reducing the unemployment rate - such as the Federal Reserve's quantitative easing program - could have the added benefit of limiting the negative consequences of long-duration unemployment through fostering faster re-employment.
Keywords: J31; J64; J68; 330